Creativity Development Oriented Poetry Text Learning Model - Fatah, Deni Abdul; Jaja Wilsa; Mascita, Dede Endang (PT Inovasi Pratama Internasional, 2025)
This research aims to: (1) produce a discovery learning model that can develop the creativity of SMP/MT students in learning poetry texts and (2) determine valid and practical criteria for the discovery learning model being developed. This study uses research and development methods with the ADDIE model (analysis, design, development, implementation, and evaluation). The steps of this research consisted of needs analysis, learning model design, learning model development, product implementation, and product evaluation. Data were collected through interviews, questionnaires, expert validation,z and student assessment. The data obtained were descriptively analyzed using a Likert scale. The research results obtained are as follows: (1) The product developed in this research is the Discovery Learning model using picture sketches that can develop the creativity of SMP/MT students in learning poetry texts. (2) The learning model development is classified as